Knowledge and Attitudes of Ecuadorian Women on Breast and Cervical Cancer Prevention - María Teresa Peñaherrera Ron; Patricio Jaramillo Guerrero; José Sixto Calvopiña del Castillo (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Background: knowledge about the prevention of breast cancer and cervical cancer and carrying out preventive examinations are fundamental elements to reduce the risk of developing the disease. Objective: to evaluate the level of knowledge about breast cancer and cervical cancer of ecuadorian women and to know their attitudes towards performing preventive examinations. Methods: a descriptive, retrospective study was carried out. The sample was made up of 297 women of different age ranges, selected at random, residing in both urban and rural areas. The technique used to collect the data was a questionnaire developed for this purpose that included open and closed questions. The results were subjected to statistical analysis. A Chi-square test was used to test for correlations in the study population. The accepted level of statistical significance was α=0.05. The results were presented in quantities and percentages. Results: the majority of women surveyed had general knowledge about cancers of the female reproductive system, but a smaller percentage was familiar with prevention principles. It was found that many women performed breast self-examinations, while a considerable number underwent mammography and breast ultrasound, with variable frequency, in addition, the majority had performed a cytological examination at least once in the last period, however, a small group of women did not remember when their last visit to the gynecologist had been. Conclusions: the women surveyed showed an adequate level of basic knowledge about the prevention of breast cancer and cervical cancer. Women living in rural areas have less information compared to those living in urban areas, although no statistically significant differences were observed. In general, ecuadorian women undergo gynecological and cytological examinations, although they use breast ultrasound and mammography less frequently. The results point to less access to these tests by women in rural areas.